Influence of XRCC1 Genetic Polymorphisms on Ionizing Radiation-Induced DNA Damage and Repair. (7th June 2010) - Sterpone, Silvia; Cozzi, Renata
Abstract : It is well known that ionizing radiation (IR) can damage DNA through a direct action, producing single- and double-strand breaks on DNA double helix, as well as an indirect effect by generating oxygen reactive species in the cells. Mammals have evolved several and distinct DNA repair pathways in order to maintain genomic stability and avoid tumour cell transformation. This review reports important data showing a huge interindividual variability on sensitivity to IR and in susceptibility to developing cancer; this variability is principally represented by genetic polymorphisms, that is, DNA repair gene polymorphisms. In particular we have focussed on single nucleotide polymorphisms (SNPs) of XRCC1, a gene that encodes for a scaffold protein involved basically in Base Excision Repair (BER). In this paper we have reported and presented recent studies that show an influence of XRCC1 variants on DNA repair capacity and susceptibility to breast cancer.